2018
DOI: 10.1002/ejic.201800219
|View full text |Cite
|
Sign up to set email alerts
|

Carba‐closo‐dodecaborates – Synthesis, Structure, and Energetics

Abstract: A full set of analytical data of salts (e.g., Me 3 NH + , Cs + , Ag + ) bearing nido- [B 11 H 14 ] -, closo-[CHB 11 H 11 ] -, and chlorinated congener [CHB 11 Cl 11 ]is reported. Structures and energetics of [CHB 11 H 11-n X n ]and [B 12 X m H 12-m ] 2-(n = 5, 11; m = 0, 12; X =

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 92 publications
0
17
0
Order By: Relevance
“…Due to the instability of NaH in air and water, the reaction required the use of a Schlenk line setup to ensure a dry and inert environment. The original procedure reported a 42% yield, but yields were later reported to be closer to 20–25%, with other studies indicating yields as low as 9% . Our own attempts found that the latter reports were correct as the reaction proved to be difficult and poorly scalable with yields of 12 and 15% when starting with 1 and 5 g of Me 3 NH­[B 11 H 14 ], respectively.…”
Section: Resultsmentioning
confidence: 73%
“…Due to the instability of NaH in air and water, the reaction required the use of a Schlenk line setup to ensure a dry and inert environment. The original procedure reported a 42% yield, but yields were later reported to be closer to 20–25%, with other studies indicating yields as low as 9% . Our own attempts found that the latter reports were correct as the reaction proved to be difficult and poorly scalable with yields of 12 and 15% when starting with 1 and 5 g of Me 3 NH­[B 11 H 14 ], respectively.…”
Section: Resultsmentioning
confidence: 73%
“…In contrast to [T 3 E] + , 10E + ,w hichf eatures no tri-coordinated silyliumi on but a bridging methyl group, is thermodynamically much less favored for both oxygen and sulfur compared to [T 3 E] + (O:1 8.1, S: 29.3 kcal mol À1 ). Since the cat-ions can be attached to differentp ositions at the carborate anion, [54] many isomers for each class of intermediates were found and activation barriers neededt ob el ocalized for each reactions tep along the reaction path. However, when [T 3 E] + is formed it needs to be transformed into 10E + in an endergonicr eactiona nd also the reactiont ot he monocation 5E + as wella st he dimerization affording 6E 2 + are all endergonic.S ince the reaction of T-E-T and T + was carried out in toluene, the reaction profile was also computed utilizingt he corresponding toluenea dducts.…”
Section: E] + + Salt Formationmentioning
confidence: 99%
“…[49] Results and Discussion Olah and Prakashe tal., [26] we have isolated this salt prior to the reaction with T-E-T,b ut not the T + -salt, since [T-H-T][B(C 6 F 5 ) 4 ]a lways forms, when [B(C 6 F 5 ) 4 ] À is the counterion. [31] Cl 11 ] À ), [54] bearing af ormally naked T + ion although strongly stabilized by ad onor-acceptor interaction with the carborate anion (vide infra, see section structure and bonding). [12,34] As imilard egradation of the [B(C 6 F 5 ) 4 ] À ionh as been reported before by Müllere tal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though chelation of ketone 4 was not observed, solvation of the sodium borohydride was observed in the 1 H NMR spectrum. 18 Experiments with another borate salt with a sodium counterion also did not support a significant amount of chelation. No change in the chemical shifts of ketone 4 was observed in the presence of NaBF 4 in either CD 3 OD or DMSO-d 6 .…”
Section: Paper Syn Thesismentioning
confidence: 96%